Experimental and numerical analysis on fire behaviour of loaded cross-laminated timber panels. Issue 1 (January 2020) - Wang, Yuexiang; Zhang, Jin; Mei, Fang; Liao, Jianan; Li, Weibin
Cross-laminated timber is a relatively new engineered timber material that can be used in the design and construction of modern timber buildings. A key factor that raises concerns in the wide application of cross-laminated timber is the uncertainty of its fire performance. This article describes experimental and numerical investigations on the fire behaviour of loaded cross-laminated timber panels manufactured with Canadian hemlock. A total of 10 cross-laminated timber panels with different number and thickness of layers were tested under ambient and standard fire conditions to investigate the flexural capacity at ambient temperature, and temperature distribution, charring rate, fire resistance, mid-span deflection under fire exposure. Three-dimensional finite element model was developed using the Hashin criterion and cohesive elements to predict the failure of wood and adhesive, respectively. The thermal model implicitly considers the rapidly increased temperature of inner fresh timber after the protective charred layers have fallen off. The numerical model was validated with the results obtained from experimental tests and was found to have the ability to simulate the fire behaviour of loaded cross-laminated timber panels in reasonable accuracy.